The curse of the King - Lerangis, Peter (New York, NY : Harper, an imprint of HarperCollinsPublishers, 2016)
Having lost Marco to the side of the Massa, friends Jack, Aly, and Cass must undo what's been done and unlock the secrets of the long lost Statue of Zeus, where they must confront gods, relive old battles, and face down their own destiny to save themselves-and the world-from destruction.
4.3
5-8
5-8
Keywords: Ability -- Juvenile fiction; Friendship -- Juvenile fiction; Statues -- Juvenile fiction; Ability -- Fiction; Friendship -- Fiction; Statues -- Fiction; Ability -- Fiction; Friendship -- Fiction; Monuments -- Fiction; Greece -- Juvenile fiction; Greece -- Fiction; Greece -- Fiction; Action and adventure fiction; Science fiction